2022
DOI: 10.1021/jacs.2c11113
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Reactivity of N–H Bonds in Triazanes and Isolation of a Triazinyl Radical

Abstract: The employment of nitrogen Lewis acids based on nitrenium cations has been increasingly featured in the fields of main group chemistry and catalysis. A formally reduced form of nitrenium D�cyclic triazanes E�are intriguing chemical compounds, the chemistry of which is completely unexplored. In this work, we reveal that N−H-triazanes exhibit unusual N−H bond properties; namely, they can serve as protons, hydrides, or hydrogen atom donors. This unique multimodal reactivity provides an N-cation, N-anion, or N-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…These unique properties of NHNs allowed us and others to demonstrate that NHNs can act as nitrogen-based Lewis acids, [29][30][31][32][33] activators of strong bonds through frustrated Lewis pair chemistry, 30,34 catalytic Lewis acids for several reactions, [35][36][37][38] photocatalysts [39][40][41] and a platform for stable nitrogen-based radicals. 42,43 Exploring this Lewis acidity, we previously demonstrated that NHN 1 reacts with phenyllithium or n-butyllithium to furnish cyclic triazanes 2 (Scheme 2b). 29 While such triazanes possess an unusual molecular structure bearing three saturated nitrogen atoms in row, their intriguing chemistry is previously unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unique properties of NHNs allowed us and others to demonstrate that NHNs can act as nitrogen-based Lewis acids, [29][30][31][32][33] activators of strong bonds through frustrated Lewis pair chemistry, 30,34 catalytic Lewis acids for several reactions, [35][36][37][38] photocatalysts [39][40][41] and a platform for stable nitrogen-based radicals. 42,43 Exploring this Lewis acidity, we previously demonstrated that NHN 1 reacts with phenyllithium or n-butyllithium to furnish cyclic triazanes 2 (Scheme 2b). 29 While such triazanes possess an unusual molecular structure bearing three saturated nitrogen atoms in row, their intriguing chemistry is previously unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These unique properties of NHNs allowed us and others to demonstrate that NHNs can act as nitrogen-based Lewis acids, 29–33 activators of strong bonds through frustrated Lewis pair chemistry, 30,34 catalytic Lewis acids for several reactions, 35–38 photocatalysts 39–41 and a platform for stable nitrogen-based radicals. 42,43…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the effectiveness of NHNs as Lewis acid catalysts to activate lone-pair donor substrates. 4 We recently discovered that NHN salts could form a photoactive CTC with its counteranion or additional Lewis base. 5 Specifically, upon visible light irradiation, the formed CTC could undergo charge transfer to generate inaccessible neutral NHN aminyl radical species.…”
Section: Introductionmentioning
confidence: 99%
“…Because the intriguing properties of 1 can be modulated by the functionalization of heteroatoms, the incorporation of nitrogen atoms into phenalenyls is also well-documented. 5 Among four monoazaphenalenyls, 2-azaphenalenyl 2 alone is known as an isoelectronic radical species of 1 . 6 Although the spin distribution of 2 is characterized by an electron spin resonance (ESR) spectrum in solution, little is known about its structural and electronic properties because of its high reactivity.…”
mentioning
confidence: 99%